To solve the equation \(-2(4x + 8) + 2x = -5x + 10\), we can arrange the steps in the correct order as follows:
-
Distribute: \(-2(4x + 8) + 2x = -5x + 10\) becomes \(-8x - 16 + 2x = -5x + 10\). (This corresponds to step 4.)
-
Combine like terms: This simplifies to \(-6x - 16 = -5x + 10\). (This corresponds to step 2.)
-
Get x-terms together on one side: Moving \(-5x\) to the left side gives \(-16 = x + 10\). (This corresponds to step 3.)
-
Get constants together on one side: Subtracting 10 from both sides leads to \(-26 = x\). (This corresponds to step 1.)
So the correct order is: 4, 2, 3, 1.